HUBUNGAN POWER OTOT TUNGKAI DAN KOORDINASI MATA DAN TANGAN DENGAN AKURASI SMASH BOLA VOLI PUTRI ATLIT PPLP PEKANBARU - Anggraini, Wita; Ramadi, Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to find out whether there is a relationship between the power of leg muscles and eye and hand coordination with the smash accuracy of the PPLP women's athlete volleyball in Pekanbaru. The population in this study amounted to 12 people. The sample in this study was PPLP 12 female volleyball athletes. By using sampling techniques, namely total sampling or sampling techniques in full, the women's volleyball team PPLP Pekanbaru athletes totaling 12 people. Results of correlation The women's volleyball team PPLP Pekanbaru athletes where the first analysis between leg muscle power X1 and Y where rtab at a significant level É‘ (0.05) = r_count (0.951)> r_tab (0.602), meaning the hypothesis is accepted and there is a strong relationship between leg muscle power to the accuracy of the women's volleyball smash at PPLP Pekanbaru athletes. From the calculation of the analysis of both X2 and Y, where r_tab at a significant level É‘ (0.05) = means r_count (0.889)> r_tab (0.602), meaning the hypothesis is accepted and there is a strong relationship between eye and hand coordination on the accuracy of PPLP athletes Pekanbaru. The third analysis of the relationship of leg muscle power (X1) eye and hand coordination (X2) with smash (Y) where rtab at a significant level É‘ (0.05) = r_count (0.953)> r_tab (0.602), it can be concluded that the relationship between (X1) and (X2) with (Y) or the relationship of leg muscle power and eye and hand coordination with smash in strong interpretations.Key Words: Power of Leg Muscles, Eye and Hand Coordination, Smash Accuracy